TEACHING AND LEARNING MEDIATED BY TECHNOLOGY - Valente, Vânia C. P. N.; Barros, Victor F. A. (Cadernos de Educação Tecnologia e Sociedade, 2020)
This issue of the Brazilian Journal of Education, Technology and Society (BRAJETS) discusses the current context of the need for education mediated by technology. In times of exceptionality in which humanity finds itself due to the social isolation caused by the dissemination of Covid-19, it is very pertinent to deepen the theme â€œTeaching and learning mediated by technologyâ€. Before only reflections were appropriate, now, more than ever, its application is imperative because, without the medium of technology, there is no way to continue academic practices. Thus, we bring some scientific contributions on this topic, which is very relevant nowadays through a set of 12 articles mostly related to the different spheres of education and teaching mediated by technology, involving both theoretical discussions and exploratory research. We invite all to enjoy a good reading of this issue, and that it can contribute with inspirations and ideas for writing and execution, whether of research or future work.